Three decades of strategic management research on M&As: Citations, co-citations, and topics - Ferreira, Manuel Portugal (2016)
Merger and acquisitions (M&As) strategies have been growingly deployed by firms for their domestic and international expansion, to redefine their business scope or take advantage of emerging opportunities. In this paper we conduct a bibliometric study of the extant strategy research on M&As, assessed by the articles published in the main journal for strategic management studies over the period 1984-2010. Results reveal the highest impact works (articles and books), the intellectual ties among authors and theories that form five main clusters of research, and the topics delved into. Performance effects, M&As as diversification strategies and RBV and capabilities-based topics have dominated the extant research. The study contributes to the extant knowledge on M&As by taking stock of the accumulated knowledge and research direction, complementing other literature reviews with a strategic management specific perspective. Thus, we provide a rear view of the field which facilitates detecting untapped gaps that may be munificent avenues for future research.